Permasalahan dubbing oleh mahasiswa dan solusinya (studi kasus proses dubbing visual novel mahasiswa Sastra Inggris IAIN Surakarta) - Pujiyanti, Umi (Institut Agama Islam Negeri IAIN Salatiga, 2017)
This research aims at figuring out what are problems faced by students when dub adapted visual novel from English to English and to know the solution coping the problems. This is descriptive qualitative research where the object is a SPARRING group consisting of 10 mentees and 2 mentor. The data gathered through observation, interview and document analysis. The results indicate that mentee tend to have improper understanding of the original story, difficulties in having clear recording, hard to pronounce words correctly and finally, making inconsistent emergence between the voice and the writing.